Antibiofilm action using water-soluble tetra-cationic porphyrin and antibacterial photodynamic therapy against Moraxella spp. from cattle. (May 2023) - Seeger, Marlane Geribone; Iglesias, Bernardo Almeida; Vogel, Fernanda Silveira Flores; Cargnelutti, Juliana Felipetto
Abstract: Infectious bovine keratoconjunctivitis (IBK) is the most important eye disease in ruminants worldwide. Moraxella bovis and Moraxella bovoculi can form biofilm and are frequently isolated from affected animals. Antimicrobials are used worldwide to treat clinical cases of IBK, although they have limited success in clearing the infection. Therefore, photodynamic therapy using porphyrins as photosensitizing molecules is an alternative method to eliminate microorganisms, including biofilms. We evaluated the antibacterial activity of a zinc(II) metalloporphyrin (ZnTMeP ) against M. bovis and M. bovoculi biofilms since this compound can efficiently inactivate planktonic Moraxella spp. This study was carried out with two reference strains of Moraxella spp. ( M. bovis : ATCC® 10900 and M. bovoculli : ATCC® BAA1259). The antibacterial activity of 4.0 μM of the ZnTMeP porphyrin was evaluated on forming and consolidate biofilms with three 30-min cycles of white-light exposure for three days. The ZnTMeP porphyrin reduced M. bovis and M. bovoculi biofilm formation. In addition, ZnTMeP partially destroyed consolidated M. bovoculi biofilms in the second white-light irradiation cycle, although the porphyrin had no effect against the consolidated biofilm of M. bovis. Despite the biofilm still not being completely inactivated, our findings are promising and encourage further experiments using the phototherapy protocol. Highlights: Photodynamic therapy is a method that can be applied to eliminate biofilms. PDT using ZnTMeP porphyrin had partial effect on biofilm formation of Moraxella spp. ZnTMeP was able to partially inactivate consolidated biofilms of M. bovoculi.